A zoologia nas escolas : percursos do ensino de zoologia em escolas da rede pública no município de Aracaju/SE - Oliveira, Crislaine de (2017)
The Teaching of Sciences has been indicated as an important foundation in the school education for the formation of the citizen with the capacity to reflect and criticize the society, giving to this one the power and the desire to collaborate in its improvement. The present research had the purpose of analyzing the conceptions of science teachers of the state public school of education of the State of Sergipe on the teaching of Zoology. In order to do so, we sought to understand some specific points about the daily life of the teacher's classroom, such as: the teachers' conceptions regarding the content of Zoology of the textbooks used in the classroom; The resources that are most used by teachers when addressing the topics in Zoology; The occurrence or not of contextualization in the teaching of zoology and the mechanisms used to reach it; And what difficulties they encounter in the exercise of teaching. The research was structured in three stages, the first consisted in the survey of articles, dissertations and theses on teaching of Zoology and its contextualization; The second stage had the purpose of collecting data related to the beginning of teaching of teachers and their difficulties in the teaching of Zoology from the application of questionnaires, with closed and open questions, to 32 professors of Sciences and Biology; And the third part involved the application of semi-structured interviews with 10 teachers from the public school system, in order to deepen the questions about the teaching of Zoology, obtained in the questionnaires. The data indicate that the majority of teachers studied here are trained in the field of Biological Sciences Degree, and a few in Biomedicine and Pedagogy. Most teachers (88%) use the textbook, but a small portion (40%) considers that the book presents the contents of Zoology in an attractive and contextualized way. Most of the teachers (90%) affirm that they use the student's daily life, bringing their life experiences to the school context, and consider that this is contextualizing the teaching; however, their testimonies show that they only want to facilitate the understanding of the student, without raising questions and solving problems that lead to the formation of critical citizens. Most teachers claim to know how to make teaching motivational, but cannot find resources in school for this. Approximately half of the teachers (52%) said they had difficulties at the beginning of teaching and of these; the majority (38%) still did not overcome them. The most used methodology is the lecture class, but for these teachers the best methodology for the teaching of Zoology is the practical classes (39%). The greatest difficulties pointed out by teachers for the teaching of Zoology, verified both in the questionnaires and in the interviews, refer to those structures of the institution and the scarce time available to work the contents, being external to the teacher figure.